2018
DOI: 10.1002/oby.22137
|View full text |Cite
|
Sign up to set email alerts
|

Young Adult Cancer: Influence of the Obesity Pandemic

Abstract: Cancer in young adults is occurring with increasing frequency. Overweight and obesity have become major public health issues reaching pandemic proportions. Excess weight is associated with increased cancer risk, morbidity, and mortality. Multiple murine models indicate that obesity not only increases cancer incidence but also accelerates its development. Thus, the possibility exists that overweight and obesity may be contributing to the appearance of specific malignancies at younger ages. This prospect, in ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
68
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(73 citation statements)
references
References 98 publications
2
68
0
3
Order By: Relevance
“…This trend has been speculated to rise continuously in the future given the lifelong exposure and with inevitable ageing. Obesity may be associated with higher risks of complications, including diabetes, hypertension, lipid disorders, and cancers in different ages [30 33]. A study found age at onset of obesity was negatively associated with risk of diabetes [34].…”
Section: Discussionmentioning
confidence: 99%
“…This trend has been speculated to rise continuously in the future given the lifelong exposure and with inevitable ageing. Obesity may be associated with higher risks of complications, including diabetes, hypertension, lipid disorders, and cancers in different ages [30 33]. A study found age at onset of obesity was negatively associated with risk of diabetes [34].…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, the inclusion of sporadic cancer cases in our cohort is possible. The immediate impact of the inclusion of sporadic cases is the presence of samples without genetic variants, which, at the same time, decrease the mean age of this group [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…The proposed pathophysiological processes related to unfavorable lifestyle factors, e.g., chronic inflammation and insulin resistance, are also established biological mechanisms associated with aging, a known risk factor for cancer development [24]. Moreover, a rising trend within the general population of being overweight appears to parallel a shift to the appearance of cancer at an earlier age [25]; this suggests that obesity and other unfavorable lifestyle factors not only promote tumor growth, but also affect aging and breast cancer onset. Hence, one may hypothesize that lifestyle factors play a role in relation to optimal breast cancer treatment, comorbidity, and breast cancer survival.…”
Section: Introductionmentioning
confidence: 99%